PENINGKATAN HASIL BELAJAR MELALUI METODE TALKING STICK PADA MATERI YESUS PEMENUHAN JANJI ALLAH KELAS VIII C DI SMP NEGERI PANCA MARGA - Anna Theresia Laju Golu Aran; Maria Selvina Kelara Welan (CV. Adiba Aisha Amira, 2025)
Classroom Action Research (PTK) on grade VIII C students at Panca Marga Junior High School which was motivated by initial observations that showed low student learning outcomes, was influenced by the learning process that still tended to be passive. This can be seen from the average score obtained from the results of the Student Worksheet (LKPD), and the lack of confidence of students to express their opinions, as well as the lack of desire of students to ask questions. So that on the subject or material about Jesus Fulfilling God's Promise, the average score obtained by students in grade VII C SMP Negeri Panca Marga is 60. The average score is still below the Minimum Completeness Criteria (KKM) set by the school, which is 75. To overcome this problem, it is necessary to apply more varied learning methods. With the application of the Talking Stick learning method, it is hoped that it can improve student learning outcomes. The purpose of this study is to find out the implementation of the Talking Stick learning method in improving the learning outcomes of students in each cycle, and to find out the learning outcomes of students in grade VIII C at Panca Marga State Junior High School through the Talking Stick learning method in the subject of Catholic Religion and Ethics in the material Jesus Fulfills God's Promise. The research method used is Classroom Action Research (PTK). This method aims to develop the most effective and efficient strategy in a scientific situation. Classroom Action Research (PTK) is carried out in four stages for each cycle, including the planning stage, implementation of actions, observation and reflection. The test result data is the data obtained from the pretest and posttest in each cycle. The results of this study showed an increase in the learning outcomes of students in the subject of Catholic Religion and Ethics in the material Jesus Fulfillment of God's Promise in class VIII C SMP Negeri Panca Marga after being subjected to action.for the learning outcomes of students in the first cycle got a percentage score of 60.26% in the category of quite good and in the second cycle got an increase in a percentage score of 100% in the category of very good. It can be concluded that the application of the Talking Stick learning method can improve students' learning outcomes in the subject of Catholic Religion and Ethics in the material Jesus Fulfills God's Promise in grade VIII C SMP Negeri Panca Marga. It is recommended that teachers can apply this Talking Stick learning method to other materials and subjects with low student learning outcomes.